ANALISIS KINERJA KEUANGAN PADA PT ASURANSI JIWASRAYA (PERSERO) PERIODE 2009- 2011 - B11108197, Kurnia Juliawanti CH (Jurnal Manajemen Update, 2014)
The purpose of this research is to know the financial performanca of PT Asuransi Jiwaasraya (Persero) and to know the factors that may influence the financial performance. That financial performance can be observed in financial report. The financial report used in this research is from 2009 until 2011. In this research, the mehtod being used is descriptive research. The analysis employed is financial ratio that consists of liquidity ratio, solvability ratio, profitability ratio, activity ratio, and growth ratio. The research result shows that overall liquidity ratio is in liquid position. Solvability ratio shows the company cant fulfill the long term debt if it relies on equity but it can pay the long term debt if it relies on asset. From the profitability ratio can be observed that the company can create big revenue only by using small equity. From the activity ratio calculation, the company performance is good enough because the company has good asset turnover and the company cn collet the account receivable in the short time. In growth ratio, the company can create stablem sales but the net income growth doesnt show good performance. The factors that may change the financial performance is the changes in the component of financial performance (internal) and external factor. Keywords: liquidity ratio, solvability ratio, profitability ratio, activity ratio, and growth ratio.